How prosocial behaviors are maintained in China: The relationship between communist authority and prosociality - Sheng, Jing; Luo, Shuilian; Jiang, Bo; Hu, Yousong; Lin, Shuang; Wang, Li; Ren, Yashi; Zhao, Chunling; Liu, Zixin; Chen, Jun (Frontiers in Psychology, 2022)
Objective: Numerous studies have demonstrated that religious belief is associated with prosocial behavior. However, how do they maintain cooperation in societies with a predominating atheist population, such as China? Different primings (explicit, subliminal, implicit) and a quasi-experiment are used to examine the link between communist authority and prosocial behaviors among college students in China. Methods: In Study 1 (N = 398), the subjects' communist authority in the university lab was primed by a communist-authority video. In Study 2 (N = 296), we compared the priming effects of communist authority and religion on prosocial intention. Study 3 (N = 311) investigated the priming effect of communist authority on prosocial behaviors by employing a scrambled sentence task in the university lab. A quasi-experiment was conducted in Study 4 (N = 313). Results: Results showed that communist-authority, a reminder of secular authorities, increased prosociality among college students. And empathy moderated the relationship between secular authorities and prosociality in Study 3 and Study 4. Discussion: Communist authority, a secular authority prime, has a positive effect on promoting prosocial behaviors. These results provided a feasible yet novel way to reveal the mechanism of the relationship between secular authorities and prosociality in China.